Views of Black women patients with obesity on desired and undesired weight‐focused clinical encounters. Issue 5 (8th June 2021) - Tucker, Carolyn M.; Roncoroni, Julia; Klein, Kirsten G.; Derias, Terry O.; Ateyah, Wafaa; Williams, Jaime; Nmezi, Nwakaego A; Shah, Nipa R.; Bilello, Lori A.; Anton, Stephen
Summary: Non‐Hispanic Black women have the highest rates of overweight/obesity of any group in the United States. To date, few interventions have worked to reduce overweight/obesity in this population. This study investigated the views of Black women with overweight and obesity treated in a primary care setting regarding desired and undesired verbal and non‐verbal behaviours by providers in provider‐patient clinical encounters focused on losing weight, maintaining weight loss, and/or obesity. Two focus groups and an individual interview (n = 15) were conducted. Qualitative data analysis yielded five distinct themes, with 11 codes (listed in parenthesis): (a) desired weight‐focused discussions (codes: Discussing weight loss with patients and discussing weight‐loss maintenance with patients), (b) desired weight‐focused support (codes: Supporting patients experiencing weight loss and supporting patients experiencing weight gain), (c) undesired weight‐focused discussions (codes: Things to avoid during weight loss discussions and things to avoid during weight gain discussions), (d) desired attitudes and behaviours during weight‐focused discussions (codes: Show caring and understanding and encourage behaviour change for weight loss), and (e) building physician‐patient rapport (codes: Enable patients to feel respected by doctors, enable patients to feel comfortable with doctors and enable patients to trust their doctors). The qualitative approach employed in this study generates a deep understanding not only of the experiences of Black women patients but also of potential strategies that physicians could employ to succeed in their discussions with patients regarding healthy weight achievement and maintenance.